Representation of Islam Identity in Khanzab: An Indonesian Horror Film - Darojat, Zakiya; Zhafirah, Salma Shafa; Putri, Ghina Alya; Zakia Darajat, Kurnia Fahma (Insaniyat: Journal of Islam and Humanities, 2025)
This study explores the representation of Islamic identity in Khanzab (2023), an Indonesian horror movie. Based on the qualitative approach and the concept of representation by Stuart Hall and islamic perspective, this study aims to show how there is a shift in Islamic identity seen from the representation in the movie. The results show that Khanzab (2023) does misrepresent Islam, the portrayal can be seen from the representation of musholla, prayer, and the Muslims shown in the movie. The depiction of musholla and mosque in the movie is seen as a place to do musyrik activities and the root of the problems. Therefore, in this movie, prayer is portrayed as a terrifying activity, where Rahayu is always disturbed by djinn; hence the prayer scene becomes the main jumpscare element in this movie. In addition, the muslim being portrayed as musyrik, who believes in djinn and black magic. In conclusion, the misrepresentation of Islamic identity is the result of commodification and commercialization to suit the interests of Indonesian audiences. Then, many movies are produced using the same strategy of portraying Islam in an obscure way just to gain popularity and profit.